Synthesis and structural-adsorption characteristics of MMS/MFI materials obtained from titanoaerosil - Rudneva, A. V.; Oranskaya, O. I.; Khomenko, K. M. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2006)
A method has been proposed of the one-stage bitemplate synthesis of mesoporous zeolite containing materials on the basis of Ti-aerosil (Ti-MZ), also the kinetics is studied of their formation and texture features. The materials obtained have been characterized by methods of IR-spectroscopy (FTIR), X-ray diffraction (XRD) and adsorption of nitrogen.